STUDI OF LITERATURE: HISTORI ISLAMIC FINANCE AND DEVELOPMENT - al Amin, Haris; Harianto, Syawal; Sabri Abd. Majid, M.; Marliyah, Marliyah; Handayani, Rita (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Islamic finance is one of the fastest growing sectors of the Islamic economy in the last two decades. This rapid development is not only driven by a religious spirit in implementing Islamic teachings, but is also motivated by pragmatic practical interests in building the people's economy. In this article the author will review how the history and background of the emergence of Islamic finance, banking practices at the time of the prophet Muhammad and his companions, banking practices in the Umayyad and Abbasid eras, banking practices in Europe and modern Islamic banking. Islamic finance stands on the foundation of Islamic sharia. Therefore, it must always be in line with sharia (sharia compliance) both in spirit and in technical aspects. In Islamic teachings, financial transactions must be free from transactions that are unlawful, with the principle of benefit (tayyib), for example free from usury, gharar, riswah and maysir. In general, it can be said that Islamic finance must follow the rules and regulations in fiqh mu'amalah. These requirements will result in a relatively substantial difference between Islamic finance and conventional finance.